The Role of Parents in Building Children's Character at Home During the Covid-19 Pandemic - Christiani Hutabarat; Sutrisno Sutrisno; Mahayoni Mahayoni; Filyensi Misriani Laufra (RERUM: Journal of Biblical Practice, 2021)
Building a child's character is very basic in a family. However, what often happens is that parents are satisfied with sending their children to Sunday school and sending them to well-known schools or schools that have a character building curriculum. However, during the Corona Virus or Covid 19 pandemic, parents can no longer leave their children in public schools or Sunday schools. The government's decision requires schools to be online. In addition, Sunday school worship is also abolished. Now they live at home with their parents almost every day. Interaction with parents is a valuable opportunity to interact and build relationships as well as build children's character. Unfortunately, many parents are not ready to seize this opportunity. This study uses a library analysis methodology and a case approach that occurred during this pandemic. The results show that parents must be aware that educating their children is very important, and is a responsibility that cannot be transferred to other parties. Being a role model in the home cannot be done once in a while but all life in the home is an example, directing the potential of children according to their talents and interests, and providing guidance and being able to become friends for them.